2016
DOI: 10.3390/rs8040330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Baseline Interferometric SAR Processors for Estimating Ground Deformation

Abstract: Abstract:The small Baseline Synthetic Aperture Radar (SAR) Interferometry (SBI) technique has been widely and successfully applied in various ground deformation monitoring applications. Over the last decade, a variety of SBI algorithms have been developed based on the same fundamental concepts. Recently developed SBI toolboxes provide an open environment for researchers to apply different SBI methods for various purposes. However, there has been no thorough discussion that compares the particular characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
(120 reference statements)
0
29
0
Order By: Relevance
“…The InSAR time series technique was largely classified by Permanent Scatterers (PS) by Ferretti et al [44,45] and Small Baseline Subsets (SBAS) by Berardino et al [46] according to the InSAR pair connection methods (i.e., 1 to 1 connection in PS and many to many in SBAS). The algorithmic improvements of time series analysis mainly aim for the densification of reliable scatterers and have proven capabilities [47]. However, according to a preliminary PS InSAR analysis, it appeared that the temporal and spatial baseline conditions between SAR images in this study were adequate to address those technical challenges with an ordinary PS algorithm, as shown in Figure 2.…”
Section: Permanent Scatterers Analyses Of Insar Pairsmentioning
confidence: 80%
“…The InSAR time series technique was largely classified by Permanent Scatterers (PS) by Ferretti et al [44,45] and Small Baseline Subsets (SBAS) by Berardino et al [46] according to the InSAR pair connection methods (i.e., 1 to 1 connection in PS and many to many in SBAS). The algorithmic improvements of time series analysis mainly aim for the densification of reliable scatterers and have proven capabilities [47]. However, according to a preliminary PS InSAR analysis, it appeared that the temporal and spatial baseline conditions between SAR images in this study were adequate to address those technical challenges with an ordinary PS algorithm, as shown in Figure 2.…”
Section: Permanent Scatterers Analyses Of Insar Pairsmentioning
confidence: 80%
“…Moreover, the single displacement measurements, computed with respect to a reference point of known motion, show a sub-centimetric accuracy, with a standard deviation of about 5 mm, consistently in both the SAR/levelling and SAR/GPS comparisons. Different SB multi-pass DInSAR tools have been developed in the recent years for the reconstruction of ground deformation [119][120][121]. A cross-comparison analysis between different SB approaches is provided in [121].…”
Section: Multi-pass Insar Techniques For the Retrieval Of Surface Dismentioning
confidence: 99%
“…Different SB multi-pass DInSAR tools have been developed in the recent years for the reconstruction of ground deformation [119][120][121]. A cross-comparison analysis between different SB approaches is provided in [121]. To illustrate the capability of the SBAS methodology, we present the results of experiments conducted for three different applications (Figures 13-15).…”
Section: Multi-pass Insar Techniques For the Retrieval Of Surface Dismentioning
confidence: 99%
“…Previous investigations have shown that other DInSAR techniques are limited in their spatial coverage, typically restricted to urban and rocky environments (e.g., Li et al, 2014;Osmanoglu et al, 2015;Gong et al, 2016). Prior studies using the ISBAS method have demonstrated that the spatial extent of ISBAS velocities is improved and the patterns of land motion correlate to geology (Sowter et al, 2013;Bateson et al, 2015).…”
Section: Quantitative Comparison Of the Measured Linear Velocitiesmentioning
confidence: 99%